2022
DOI: 10.3390/molecules27154678
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Herbicidal (Phytotoxic), Antioxidants Potential of Essential Oils from Calycolpus goetheanus (Myrtaceae) Specimens, and in Silico Study

Abstract: The essential oil (EO) of Calycolpus goetheanus (Myrtaceae) specimens (A, B, and C) were obtained through hydrodistillation. The analysis of the chemical composition of the EOs was by gas chromatography coupled with mass spectrometry CG-MS, and gas chromatography coupled with a flame ionization detector CG-FID. The phytotoxic activity of those EOs was evaluated against two weed species from common pasture areas in the Amazon region: Mimosa pudica L. and Senna obtusifolia (L.) The antioxidant capacity of the EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
0
7
1
1
Order By: Relevance
“…Regarding the inhibitory effects on root elongation, the EO of Xfru showed the highest inhibition potential at 55.22 ± 2.72% ( M. pudica) , while for S. obtusifolia , the value was 60.43 ± 4.63%. The present results are different from those observed by Franco et al [ 24 ] for the EO from Calycolpus goetheanus specimen C, which showed inhibition values of 33.33 ± 5.77% and 6.67 ± 5.77% for M. pudica and S. obtusifolia , respectively.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the inhibitory effects on root elongation, the EO of Xfru showed the highest inhibition potential at 55.22 ± 2.72% ( M. pudica) , while for S. obtusifolia , the value was 60.43 ± 4.63%. The present results are different from those observed by Franco et al [ 24 ] for the EO from Calycolpus goetheanus specimen C, which showed inhibition values of 33.33 ± 5.77% and 6.67 ± 5.77% for M. pudica and S. obtusifolia , respectively.…”
Section: Resultscontrasting
confidence: 99%
“…S. obtusifolia also causes toxicity in cattle [ 22 ]. Recent studies investigated the phytotoxic potential of EOs on these two invasive species with the aim of benefiting local agroindustry [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Stefanello et al 2011;Cascaes et al 2015). In a previous study of the EOs leaves composition, Calycolpus goetheanus (Myrtaceae) presented -cadinol (9.03%) (Franco et al, 2022), and germacrene D was characterized by the EOs of M. tomentosa (11.45%) (Franco et al, 2021). Ledol was characterized in the leaves of M. hatschbachii D.…”
Section: Resultsmentioning
confidence: 89%
“…Among eight products of SchTPS6, all seven previously elucidated compounds including 7 , , 9 , 15 , 22 , , 24 , 26, , and 27 , ,, possess insecticidal, fungicidal, and/or herbicidal activities (Figure A, C). Hence, we sought to enhance their production in yeast, which may lay a foundation for the development of agrochemical mixtures.…”
Section: Resultsmentioning
confidence: 97%
“…Intriguingly, seven out of eight products of SchTPS6 in S. cerevisiae were reported to have insecticidal, fungicidal, and/or herbicidal activities. ,, We next constructed an engineered S. cerevisiae in which the titers of two major products α-cadinol and τ-muurolol reached 46.2 ± 4.0 and 11.2 ± 1.4 mg/L, respectively.…”
Section: Introductionmentioning
confidence: 99%